“Painting oneself out of a corner” – Exploring the use of art in a Child and Adolescent Psychiatry setting - Bøgh Laura; Andersen Susie; Ditte R. Hulgaard (Nordic Journal of Arts, Culture and Health)
Background: Eating disorders and functional disorders are severe conditions. Nonverbal treatment approaches, including the use of art, have emerged as promising supplements for the treatment of these patients. Purpose: This qualitative interview study aims to explore how youths with eating and functional disorders experience participation in an art project in a Child and Adolescent Psychiatric setting. Methodology: The participants were three youths who had actively participated in the art project “Painting oneself out of a corner”. Semi-structured interviews were conducted and subsequently analyzed using interpretative phenomenological analysis. Findings: Three main themes were identified in the analysis: Enhancing self-discovery describes how the youths unfold personal themes using art. To be seen illustrates how the art project makes the youths feel seen as more than a patient. Finally, A land we can all set foot on describes how art can facilitate different aspects of communication. Value: This study provides new perspectives to support the use of art as a supplement to traditional treatment approaches for youths with an eating or functional disorder in psychiatric settings and encourages further research in this field.